Capital requirements, market structure, and heterogeneous banks - Müller, Carola (Halle Institute for Economic Research (IWH) - Member of the Leibniz Association, 2022)
Bank regulators interfere with the efficient allocation of resources for the sake of financial stability. Based on this trade-off, I compare how different capital requirements affect default probabilities and the allocation of market shares across heterogeneous banks. In the model, banks‘ productivity determines their optimal strategy in oligopolistic markets. Higher productivity gives banks higher profit margins that lower their default risk. Hence, capital requirements indirectly aiming at highproductivity banks are less effective. They also bear a distortionary cost: Because incumbents increase interest rates, new entrants with low productivity are attracted and thus average productivity in the banking market decreases.
urn:nbn:de:gbv:3:2-880694
Keywords: Graue Literatur; bank competition; bank regulation; Basel III; capital requirements; heterogeneous banks; leverage ratio